Serum Copeptin as the Predictor for Acute Heart Failure Complication of Acute Myocardial Infarction in Patients with ST-Segment Elevation - Ardi Putranto Ari Supomo; JB. Suparyatmo; Dian Ariningrum (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Acute Myocardial Infarction (AMI) is necrotic cardiac muscle cells due to unstable ischemic syndrome. Therapy monitoring is needed because various complications may occur (Heart Failure/HF). ST-Segment Elevation Myocardial Infarction (STEMI) can develop to Acute Heart Failure (AHF) due to myocardial dysfunction, transmural heart disease, pathological cardiac remodeling. Copeptin is an antidiuretic hormone which increases in the cardiac event. It can be used as a predictor of a further cardiac event. This study aimed to determine the role of serum copeptin level as a predictor of AHF complication in STEMI patients. A prospective cohort study was performed in 85 adult STEMI patients admitted to The Clinical Pathology Installation of Dr. Moewardi Hospital, Surakarta. Data with normal and abnormal distribution were presented in mean±Standard Deviation (SD) and median (min-max), respectively. Statistical analysis was performed using Kolmogorov-Smirnov, bivariate, and multivariate analysis for RR with Confidence Interval (CI) of 95% and p < 0.05 was considered significant. The copeptin cut-off point was determined using the ROC curve. Bivariate and multivariate analysis showed a higher copeptin level in STEMI patients with AHF compared to that of non-AHF (RR=5.172, CI 95% 1.795-14.902, p=0.002 and RR=1.889, CI 95% 1.156-3.086, p=0.001; respectively). The STEMI patients with an elevated level of copeptin showed an increased risk of AHF (STEMI with elevated copeptin level vs STEMI with normal copeptin level; 28.74% vs. 88.91%). Copeptin level is significantly related to AHF complication in STEMI patient, the higher level of copeptin led to the higher the risk of AHF.